2014
DOI: 10.1073/pnas.1417294111
|View full text |Cite
|
Sign up to set email alerts
|

The rare DAT coding variant Val559 perturbs DA neuron function, changes behavior, and alters in vivo responses to psychostimulants

Abstract: Despite the critical role of the presynaptic dopamine (DA) transporter (DAT, SLC6A3) in DA clearance and psychostimulant responses, evidence that DAT dysfunction supports risk for mental illness is indirect. Recently, we identified a rare, nonsynonymous Slc6a3 variant that produces the DAT substitution Ala559Val in two male siblings who share a diagnosis of attention-deficit hyperactivity disorder (ADHD), with other studies identifying the variant in subjects with bipolar disorder (BPD) and autism spectrum dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
113
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(125 citation statements)
references
References 101 publications
(115 reference statements)
8
113
1
1
Order By: Relevance
“…These findings indicate that DAT Val559 exists in a state where D2-dependent PKCb action drives transporter-mediated DA export in a manner that is normally impeded with wild-type DAT, either because D2 receptors are not continually flooded by DA leak or because other inhibitory processes are in place (that must then also be lost in the variant). Recently, Mergy et al (2014) reported studies with DAT Val559 mice, providing evidence of both excessive extracellular DA and tonic presynaptic D2 receptor stimulation. The availability of the DAT Val559 mouse model provides an unprecedented opportunity to define the significance of D2 receptor mediated PKCb signaling for DAT modulation in vivo.…”
Section: Regulation Of Dopamine Transporter Membranementioning
confidence: 99%
See 1 more Smart Citation
“…These findings indicate that DAT Val559 exists in a state where D2-dependent PKCb action drives transporter-mediated DA export in a manner that is normally impeded with wild-type DAT, either because D2 receptors are not continually flooded by DA leak or because other inhibitory processes are in place (that must then also be lost in the variant). Recently, Mergy et al (2014) reported studies with DAT Val559 mice, providing evidence of both excessive extracellular DA and tonic presynaptic D2 receptor stimulation. The availability of the DAT Val559 mouse model provides an unprecedented opportunity to define the significance of D2 receptor mediated PKCb signaling for DAT modulation in vivo.…”
Section: Regulation Of Dopamine Transporter Membranementioning
confidence: 99%
“…Indeed, AMPH lacks the ability to trigger DA efflux in the DAT Val559 mutant, serving rather to attenuate elevated basal efflux (Mazei-Robison et al, 2008). Recently, Mergy et al (2014) provided in vivo evidence via microdialysis studies of knock-in mice that the DAT Val559 variant supports a tonic elevation in basal extracellular DA, consistent with chronic DATmediated DA efflux, although whether CaMKII sustains DAT Val559 efflux activity in vivo has yet to be addressed.…”
Section: A Regulation Of Dopamine Transporter Bymentioning
confidence: 99%
“…However, humans that are homozygous for loss-offunction DAT (SLC6A3) alleles present with a complex disorder that resembles PD, rather than ADHD (see section V.B; Kurian et al, 2011;Ng et al, 2014). Instead, clinical studies that genetically screen individuals with ADHD, as well as preclinical studies using cell lines and genetic mouse models, have suggested that variations in the genes encoding for DAT, rather than simple loss of function, and/or DA receptors are associated with risk for ADHD (Gill et al, 1997;Bobb et al, 2005;Mazei-Robison et al, 2005;Sakrikar et al, 2012;Mergy et al, 2014). Importantly, only a few human case studies of DAT variants have been implicated in ADHD to date.…”
Section: Dopamine Transporter Vesicular Monoaminementioning
confidence: 99%
“…Furthermore, in vitro experiments with transfected cells formed the basis for many genetic mutations that were later engineered in mice, which now serve for in vivo investigations of psychoactive drugs or as preclinical models of mental disorders (Henry et al, 2006;Mazei-Robison et al, 2008;Prasad et al, 2005). For example, in vitro experiments allowed the construction of a transgenic mouse model with a 5-hydroxytryptamine (5-HT [serotonin]) transporter (SERT) mutation for the in vivo assessment of SERT-mediated effects of antidepressants or cocaine (Prosser et al, 2014;Thompson et al, 2011) or to shed light on functional abnormalities of the DAT variant Val559, which is being investigated as a potential mouse model of attention-deficit hyperactivity disorder (Mergy et al, 2014).…”
Section: Methods For Studying Transporter and Receptor Pharmacology Imentioning
confidence: 99%
“…We initially followed this protocol (Hysek et al, 2012c) but later adapted it according to the principles reported by Scholze et al (Scholze et al, 2000), who used a superfusion system. The superfusion system is preferentially used for rodent tissue slices that are preloaded with radioactive transporter substrates (Mergy et al, 2014), but it can also be adapted for transfected cells (Pifl et al, 1995;Scholze et al, 2000). Transfected cells are grown on coverslips and loaded with radioactive substrates.…”
Section: Methods For Studying Transporter and Receptor Pharmacology Imentioning
confidence: 99%